Adipose/Connective Tissue From Thyroid-Associated Ophthalmopathy Uncovers Interdependence Between Methylation and Disease Pathogenesis: A Genome-Wide Methylation Analysis - Liang, Yu; Ding, Sijia; Wang, Xiying; Hu, Chunchun; Zhang, Yihan; Hu, Yan; Zhang, Yuye; Kong, Hongyu; Xia, Weiyi; Jing, Qinghe; Hu, Yuxiang; Zhao, Chen; et al. (Frontiers in Cell and Developmental Biology, 2021)
In response to pathological stimulation, methylation status conversion of the genome drives changes of cell feature and is able to promote disease development. Yet the role of methylation in the development of thyroid-associated ophthalmopathy (TAO) remains to be evaluated. Overexpansion of orbital tissue is the key feature of thyroid-associated ophthalmopathy. In this study, the methylation profile of orbital adipose/connective tissue from TAO patients and normal individuals were compared. After screening 3739 differentially methylated probes, the distribution and properties of these probes were analyzed. Furthermore, enriched biological functions of these genes associated with differential methylation and the relationship between their methylation status and expression profile were also identified, including PTPRU and VCAM-1. According to our results, methylation was involved in disregulated immune response and inflammation in TAO and might contribute to activation of fibroblast and adipogenesis, leading to the expansion of orbital tissue. Neuropathy and neurobehavioral symptoms were also potentially associated with methylation. These results may help to extend the understanding of methylation in TAO and provide more insights into diagnosis and treatment of patients.